Aesthetics of Written Batik Motif “Chongyang” Identix Batik - Ari Eko Budiyanto; Rina Purwanti (Formosa Journal of Sustainable Research, 2023)
Batik is a work of art made using canting and wax. Hand-drawn batik is made by manually attaching cantings to cloth. The Chongyang batik motif is taken from a traditional fermented drink typical of Semarang. This motif is an interesting design to study. The research aims to reveal the aesthetics of written batik with the chongyang motif. The approach used is aesthetics which includes Unity, Dominance, and Balance. This research uses descriptive analysis method. The data source for this research is the “chongyang” motif. Samples were taken from the literature and then analyzed with an aesthetic approach. The results show that the Chongyang batik motif has beauty and contains three aesthetic elements. Chongyang motifs, tropical plants, and balanced color combinations add to the aesthetic impression and originality of works using manual techniques, namely by hand